2019
DOI: 10.1016/j.trecan.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Cell Culture Medium Formulation and Its Implications in Cancer Metabolism

Abstract: Historic cell culture media were designed to ensure continuous cancer cell proliferation in vitro. However, their composition does not recapitulate the tumor's nutritional environment. Recent studies show that novel media formulations alleviate the non-physiological constraints imposed by historic media, and lead to cell culture results more relevant to tumor metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 16 publications
3
87
1
Order By: Relevance
“…Interestingly, we also found that TLR3 but not TLR4 associated mitochondrial reprogramming was dependent on glucose availability in the microenvironment. Supra-physiological levels of glucose have been shown to decrease a cell's dependence on mitochondria for energy production 52,64 . Similarly, our results suggest high glucose conditions may also alter mitochondr ia l reprogramming associated with TLR3 engagement.…”
mentioning
confidence: 99%
“…Interestingly, we also found that TLR3 but not TLR4 associated mitochondrial reprogramming was dependent on glucose availability in the microenvironment. Supra-physiological levels of glucose have been shown to decrease a cell's dependence on mitochondria for energy production 52,64 . Similarly, our results suggest high glucose conditions may also alter mitochondr ia l reprogramming associated with TLR3 engagement.…”
mentioning
confidence: 99%
“…A combination of the above explanations most likely contributes to the cultured cells versus primary tumor discrepancy. It is already well-established that cell culture conditions do not always accurately reflect physiological conditions (Ackermann and Tardito, 2019;Sanderson et al, 2019;Vande Voorde et al, 2019). Prior to in vitro metabolomics profiling, we cultured our cells using heat-inactivated fetal bovine serum which, thereby nullifying any MTAP-activity that would otherwise be present in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vitro screens of human cells have been performed in traditional media that poorly recapitulate metabolite availability in human blood. (Ackermann and Tardito, 2019;Cantor, 2019).…”
Section: Introductionmentioning
confidence: 99%